PELAKSANAAN NILAI PASIDIKARAN MASYARAKAT KECAMATAN KUTA KABUPATEN BADUNG PADA ERA MODERN - Purnami Azhari, Dewa Ayu; Bagus Suka Arjawa, I Gusti Putu; Sastri Mahadewi, Ni Made Anggita (JURNAL ILMIAH SOSIOLOGI (SOROT), 2020)
Pasidikaran value is the traditional customary value of Balinese society, which in its implementation is based on the practice of the Tri Hita Karana concept. The strength in its implementation can even be seen in Kuta District, Badung Regency. This research was also conducted aimed at analyzing the implementation of market values by the people of Kuta in the modern era and benefits obtained. This research uses a qualitative approach with descriptive and explorative types. The theory used in this research is the cultural theory of the Jan Nedeveen Pieterse with a cultural hybridation paradigm. As for the implementation it continues to take place properly in accordance with the awig-awig and pararem of each traditional village and traditional banjar. Although in the process of implementing it, several modifications were made as a form of adjustment to the current situation of the community. Keywords: Pasidikaran Value, Kuta Sub-District Community, Modern Era